Soil mechanics and foundations - Budhu, Muni. (New York ; Chichester : John Wiley and Sons, 2000)
This book presents the principles of soil mechanics and its application to foundation analyses.
Keywords: Soil mechanics; Foundations; Foundations; Soil mechanics